Numerical and Experimental Study on Heat Transfer Enhancement by Vortex Generation - M. Jalil, Jalal; A. Ismeal, Khalid; T. Ahmed, Sabah (Journal of Engineering and Sustainable Development, 2006)
Numerical and experimental study was carried out on heat transfer enhancement using a slender delta wing vortex generator to generate longitudinal vortices in a rectangular duct. Numerically, laminar with constant wall temperature was considered. Effect of angle of attack of the wing (from 0.0 to 56.5 degree) on the Spain-wise average Nusselt number and the span wise average skin friction coefficient were investigated. Numerical results demonstrate similar behavior to the published results of other investigators. Experimentally, effect of angle of attack (from 0.0 to 56.5 degree) of the vortex generator, wing aspect ratio of the vortex generator (from 0.5 to 2.0) and wing width to duct width (from 0.25 to 0.5) on the heat transfer process for laminar flow (Re = 750 to 2700)and turbulent flow (Re = 4100 to 7950) were investigated. Both numerical and experimental results show the enhancement of heat transfer but experimental results show higher values of Nusselt number compared with the numerical results.